Undergraduate pharmacy students’ attitudes and perceived barriers toward provision of pharmaceutical care: a multi-institutional study in Nepal - Baral SR; Parajuli DR; Shrestha S; Acharya SR; Dahal P; Poudel P; Ghimire S; Palaian S; Shrestha N (Dove Medical Press, 2019)
Sanjay Raj Baral1,* Daya Ram Parajuli,2,* Shakti Shrestha,3,* Santosh Raman Acharya,4 Prasanna Dahal,5 Prakash Poudel,6 Saruna Ghimire,4 Subish Palaian,7 Naveen Shrestha81Department of Pharmacy and Pharmacology, Chitwan Medical College, Bharatpur-10, Chitwan, Nepal; 2School of Nursing and Health Sciences, Flinders University, Adelaide, Australia; 3School of Pharmacy, University of Queensland, Brisbane, QLD, Australia; 4Department of Pharmacy, Valley College of Technical Sciences, Kathmandu, Nepal; 5Department of Pharmacy, College of Medical and Allied Sciences, Purbanchal University, Gothgaun, Morang, Nepal; 6Department of Pharmacy, Novel Academy, Pokhara-8, Nepal; 7College of Pharmacy, Gulf Medical University, Ajman, UAE; 8CiST College, Kathmandu, Nepal*These authors contributed equally to this work Background: Pharmaceutical care (PC) has a significant impact on optimizing pharmacotherapy and improving patients’ quality of life. We aimed to determine the attitudes and perceived barriers of final year pharmacy undergraduates towards provision of PC services in Nepal.Methods: A cross-sectional study was conducted among 232 students using a 13-item-standard PC attitude survey (PCAS) questionnaire and 12-itemed PC barrier questionnaires. Mann–Whitney U test and Kruskal–Wallis tests were used to measure the median difference between groups, at alpha=0.05, and Spearman’s rho test was used to measure the strength of the correlation.Results: Majority of students were self-motivated in undertaking the current pharmacy education (178, 76.7%) and had no previous incomplete grades that could delay their graduation (177, 76.3%). Over 80% of students had a positive attitude toward all items of PCAS (agreed and strongly agreed) except for two items. Whereas, 61 (26.3%) disagreed and strongly disagreed that providing PC takes too much time and effort. The major barriers perceived were inadequate PC training (176, 75.9%), inadequate drug information resources in the pharmacy (170, 73.3%), and lack of access to patient medical records in the pharmacy (165, 71.1%). A significant relationship was noticed between positive attitude towards PC and three factors; source of motivation, current employment in pharmacy job, and incomplete grades delaying graduation. Age factor was significant but negatively correlated with the scores of positive attitudes namely “I would like to perform PC as a pharmacist practitioner”, “Providing PC is professionally rewarding” and “I feel that the PC is the right direction for the provision to be headed”.Conclusion: Nepalese undergraduate pharmacy students had positive attitudes toward PC. Exercising proper pharmacy practice regulations and educational efforts to overcome the perceived barriers may lead to better delivery of PC.Keywords: pharmacy practice internship, pharmaceutical care, undergraduate pharmacy student, Nepal